Considerations of how to conduct meta-analyses in psychological interventions. (4th May 2018) - Flückiger, Christoph; Del Re, A. C.; Barth, Jürgen; Hoyt, William T.; Levitt, Heidi; Munder, Thomas; Spielmans, Glen I.; Swift, Joshua K.; Vîslă, Andreea; Wampold, Bruce E.
Abstract : Clinical or methodological significance of this article: Meta-analysis is a powerful tool for resolving conflicting conjectures or findings while also providing a critical overview of a scientific area.